Family-Focused Rural Early Intervention Personnel Preparation: Family Stories and Student Development - Gretchen Butera (Journal of Research in Rural Education, 1998)
Circumstances ofpractice in rural communities and the rapidly changing professional environment ofearly intervention present challenges to effective personnel preparation. Case study and ethnographic methods used in the context of student-family field-based experiences appear promisingfor guiding students in understanding family perspectives and in developing personal theories about early interventions in rural settings. These personnel preparation processes have the effect ofhelping students engage in a life-long process of establishing their own professional identities.